EKSTRAK HEKSAN BIJI JINTAN HITAM (Nigella sativa L) MENINGKATKAN AKTIVITAS FAGOSITOSIS MAKROFAG TIKUS BETINA GALUR SD (Sprague Dawley) YANG DIINDUKSI DMBA (7,12Dimetilbenz(Î±)antrasen) SECARA IN VITRO - Akrom Akrom; Fatimah Fatimah (Pharmaciana, 2015)
Previous research has shown that black cumin seed oil is as an immunomodulator, but the mechanism MBJH as an immunomodulator in DMBA-induced macrophage unknown. A study to determine the effects of EHBJH on the activities of SD rat peritoneal macrophage phagocytosis induced DMBA has been conducted. This study was conducted on 10 female Sprague Dawley rats were divided into two groups, namely 5 mice without any treatment group and 5 mice DMBA DMBA treatment groups. Once a week administration of 15 mg DMBA of mice,rats dissected and taken peritonealnya fluid for isolation of macrophages to be cultured for 24 hours. The peritoneal macrophages were given hexane BJH (Nigella sativa Lour) as much as 1 mg/mL, 5 mg/mL, 25 mg/mL, and were given a standard timokuinon for each group without induction DMBA and DMBA treatment groups. Macrophages were incubated for 2 hours back. Phagocytosis test is done by adding the latex particles on cultured macrophages and Giemsa staining. Data percentage of macrophages that eat latex and phagocytosis index were analyzed using the Kolmogorov-Smirnov test followed by ANOVA and LSD test with a 95% confidence level. The results showed that the activity and phagocytosis index DMBA -induced macrophages that is not greater than the index of activity and macrophage phagocytosis induced macrophages (p<0.05). A group of 25 mg/mL EHBJH have activity and phagocytosis index is highest when compared with the other treatment group (p<0.05).  Conclusion: The study showed that the hexane BJH (Nigella sativa Lour) can improve macrophage phagocytic activity of female rats Sprague Dawley strain.